Incorporation of ZnCl2 into an etch-and-rinse adhesive system on flexural strength, degree of conversion and bond durability to caries-affected dentin - Rodrigues Oliveira, Cerida Aurelia; Peixoto Campos, Rosa Maria; Campos Macedo, Julia Peixoto; Silva, Anderson Rodrigo; Candid Maximo, Leandro Neriton; Silva, Tania Mara [UNESP]; Gomes Franca, Fabiana Mantovani; Basting, Roberta Tarkany; Turssi, Cecilia Pedroso; Paiva Goncalves, Sergio Eduardo de [UNESP]; Botelho Amaral, Flavia Lucisano (Mosher & Linder, Inc, 2019)
Purpose: To evaluate the effect of a zinc chloride (ZnCl2) solution (2% wt), incorporated into a two-step etch-and-rinse adhesive system (AS), on microtensile bond strength (mu TBS) to caries-affected dentin (CAD). Methods: First, the degree of conversion (DC) of the AS with and without the ZnCl2 solution was evaluated by Fourier transform infrared spectroscopy (FTIR). Second, beam-shaped samples (7 mm x 2 mm x 1 mm) were prepared with the AS containing the ZnCl2 solution to perform flexural strength (FS) tests. For mu TBS testing purposes, CAD surfaces were etched with phosphoric acid and randomly divided into three groups (n=10): ZnCl2 - AS with ZnCl2; NT (no treatment)-AS without ZnCl2; and CHX - pretreatment with 2% chlorhexidine solution. AS (Adper Single Bond 2) was applied according to the manufacturer's instructions, and resin composite restorations were built up. After 24 hours, the resindentin blocks were sectioned into specimens (0.8 mm 2 ), and then subjected to mu TBS testing immediately following, or after 6 or 12 months of water storage (WS). The adhesive interface was evaluated by scanning electron microscope. Both mu TBS and FS tests were performed using a universal testing machine (0.5 mm/minute). FS and DC data were submitted to the Student t-test, and mu TBS data were subjected to two-way ANOVA and Tukey's test (alpha= 0.05). Results: DC was not affected by ZnCl2 incorporation into AS (P= 0.2527). Higher FS values were obtained in the group with ZnCl2 added to AS. Regarding mu TBS, the mean of the NT group was statistically higher than that of the ZnCl2 or the CHX groups (P< 0.001), regardless of WS, but the latter groups did not differ from each other. mu TBS at 24 hours was statistically superior to that of 6 and 12 months of WS (P< 0.001).